Randomized study of probiotics in primary care. Issue 3 (18th June 2014) - Patel, Jasmeeta; Curry, William J; Graybill, Marie A; Bernard, Shaina; McDermott, Anna S; Karpa, Kelly
Abstract: Objectives: Several studies have demonstrated that probiotics can be helpful in preventing antibiotic-associated diarrhoea in hospitalized patients. However, the extent to which probiotics may benefit healthy adults taking a course of antibiotics has not been investigated in primary care . Furthermore, patient willingness to take a probiotic supplement concomitantly with antibiotics has not been explored. We aimed to conduct an exploratory study using probiotics in adults requiring an acute course of antibiotic therapy. Methods: Patients prescribed antibiotics for treatment of acute infections in an outpatient family practice setting were randomized to receive either a probiotic or placebo concurrently. Patients completed adherence diaries and daily symptom checklists to assess gastrointestinal and vaginal (women) symptoms and collect information about adherence. Key findings: During 179.5 h in which patients were actively recruited, 952 individuals sought care at the family practice clinic. Of these individuals, 124 were prescribed oral antibiotics; ultimately, 51 individuals met eligibility criteria, consented to participate and were randomized. Forty participants (78.4%) returned symptom diaries. No adverse effects were reported from probiotic use; however, adherence was better with the prescribed antibiotic regimen than with the study supplement ( P = 0.0033). Conclusion: In our pilot study, probiotics were well tolerated, although no differences were detected in any gastrointestinal or vaginal symptoms between probiotic or placebo.